دور العنف اللفظي في تدعيم الرسالة الاتصالية لدي الجمهور الجزائري - غرايسة، إسماعيل, غرايسة، عثمان (جامعة الوادي university of Eloued, 2020)
الملخص: دور العنف اللفظي في تدعيم الرسالة الاتصالية لدى الجمهور الجزائري نظرا للدور الذي تأدية وسائل الاتصال في التوعية و التأثير في الاتجاهات و السلوكيات و نظرا لأهمية هذا الموضوع من وسائل التواصل الحديثة فقد جاءت هذه الدراسة بهدف الكشف عن مدى انتشار العنف اللفظي عبر وسائل الاتصالية و الرسائل المختلفة و اعتمدت هذه الدراسة على المنهج المسحي لاستمارة الاستقاء لعينة من جامعة الشهيد حمه الاخضر بالوادي Abstract: The role of verbal violence in strengthening the communication message among the Algerian public due to the role played by the means of communication in raising awareness and influencing trends and behaviors, and given the importance of this topic of modern means of communication, this study came with the aim of revealing the extent of verbal violence spread through the means of communication and various messages This study was based on the survey method of the intake form for a sample from the University of Shaheed Hama Al-Akhdar in the valley
- درسة ميدانية لعينة من طالبة جامعة الشهيد حمه لخضر بالوادي -
مذكرة ماستر إعلام واتصال تخصص سمعي بصري
Keywords: الاتصال، العنف اللفظي; Communication, violence verbale; Communication, verbal violence